Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-51845-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ecology of male hippopotamus in a changing watershed

Abstract: The obligate dependency of the common hippopotamus, Hippopotamus amphibius, on water makes them particularly vulnerable to hydrological disturbances. Despite the threats facing this at-risk species, there is a lack of information regarding H. amphibius spatial ecology. We used high-resolution tracking data of male H. amphibius to assess home range size, movement mode (e.g. residency and migratory movements), and resource selection patterns. We compared these results across seasons to understand how hydrologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 57 publications
3
38
2
Order By: Relevance
“…Hippos itself does have a fairly wide home range of 50-500 hectares or a radius of 300 m. While the roaming ability of hippos is known to be quite far too. Even Stears et al (2019) reported H. amphibious walking distance of 15 km. Roth et al (2004) observed that C. liberiensis was able to travel long distances downstream.…”
Section: Resultsmentioning
confidence: 99%
“…Hippos itself does have a fairly wide home range of 50-500 hectares or a radius of 300 m. While the roaming ability of hippos is known to be quite far too. Even Stears et al (2019) reported H. amphibious walking distance of 15 km. Roth et al (2004) observed that C. liberiensis was able to travel long distances downstream.…”
Section: Resultsmentioning
confidence: 99%
“…Changing water availability is a key mechanism that drives the exploratory and migratory movement modes of H. amphibius (Stears et al 2019). This landscape change can influence disease dynamics by altering contact rates between susceptible individuals and B. anthracis reservoirs (e.g., Ostfeld et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…the Thamalakane River), are clearly mapped (Figure 3). Access to high spatial resolution maps is also important for spatial planning [28][29][30], assessing land use change [31][32][33], water resource planning [34,35], and wildlife habitat studies [36][37][38].…”
Section: Discussionmentioning
confidence: 99%